X-ray absorption spectroscopy evidence of sulfur-bound cadmium in the Cd-hyperaccumulator Solanum nigrum and the non-accumulator Solanum melongena. (15th June 2021) - Pons, Marie-Laure; Collin, Blanche; Doelsch, Emmanuel; Chaurand, Perrine; Fehlauer, Till; Levard, Clément; Keller, Catherine; Rose, Jérôme
Abstract: It has been proposed that non-protein thiols and organic acids play a major role in cadmium phytoavailability and distribution in plants. In the Cd-hyperaccumulator Solanum nigrum and non-accumulator Solanum melongena, the role of these organic ligands in the accumulation and detoxification mechanisms of Cd are debated. In this study, we used X-ray absorption spectroscopy to investigate Cd speciation in these plants (roots, stem, leaves) and in the soils used for their culture to unravel the plants responses to Cd exposure. The results show that Cd in the 100 mg kg −1 Cd-doped clayey loam soil is sorbed onto iron oxyhydroxides. In both S. nigrum and S. melongena, Cd in roots and fresh leaves is mainly bound to thiol ligands, with a small contribution of inorganic S ligands in S. nigrum leaves. We interpret the Cd binding to sulfur ligands as detoxification mechanisms, possibly involving the sequestration of Cd complexed with glutathione or phytochelatins in the plant vacuoles. In the stems, results show an increase binding of Cd to –O ligands (>50% for S. nigrum ). We suggest that Cd is partly complexed by organic acids for transportation in the sap. Graphical abstract: Image 1 Highlights: X-ray absorption Cd speciation in Solanum nigrum and S. melongena was reported . Cd in the pre- and post-culture clayey loam soils was bound to iron oxyhydroxides. In S. melongena roots and fresh leaves, Cd was fully bound to thiol ligands. In S. nigrum leaves, Cd detoxification involved binding to thiols and inorganic S. In both plants, Cd transportation involved partial complexation with organic acids. Abstract : Cadmium speciation in Solanaceae was investigated using X-ray absorption spectroscopy. Results showed evidence of Cd detoxification through Cd binding with thiols and inorganic sulfur.